Nuevas metodologías para el diagnóstico y la jerarquización de atractivos turísticos en el Ecuador: Caso de estudio cantón Catamayo, provincia de Loja - Vite Valverde, Freddy Michael (2018)
The Career of Gestión Turística y Medio Ambiente de la Universidad Internacional del Ecuador –Extension of Loja, with the aiming to contribute significantly to the tourism enlargement in the Province, the university is developing an integral research project; thus, it has been considered as a general objective to propose alternatives for the promotion of tourism opportunities in the sector under study. The work process has been carried out in three phases: 1) Bibliographical compilation, 2) Survey of field information and 3) Hierarchy of attractions.The obtained results after this process are as follows: Catamayo Tourist cadaster update, diagnosis of natural and cultural attractions of the area, and hierarchy of attractions, using as a methodology the guide for the survey of tourist attractions of Ecuador 2017, and Methodology guide for the Attractions Hierarchy, and generating tourist spaces established by the Tourist Ministry of Ecuador.